2017
DOI: 10.1002/pola.28744
|View full text |Cite
|
Sign up to set email alerts
|

Lignin‐based polymers via graft copolymerization

Abstract: Lignin is an important source of synthetic materials because of its abundance in nature, low cost, stable supply, and no competition to the human food supply. Lignin, a crosslinked phenolic polymer, contains a large number of aromatic groups that can be used as a substitute for petroleum-based aromatic fine chemicals. However, modification of lignin is necessary for its application in advanced materials due to its chemically inert nature and structural complexity. Polymeric modification of lignin via graft cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 96 publications
(138 reference statements)
0
82
0
Order By: Relevance
“…18,19 Current lignin research strategies follow two main routes: rst, a direct utilization without chemical modication and second, pre-treatment including chemical modication, functionalization and/or fractionation (degradation) to generate a wide range of intermediates, ne chemicals and polymers. [20][21][22] In between, lignin-derived polymers and composites are also studied as potential materials for biomedical applications such as tissue engineering and drug release. [23][24][25] Due to the large number of hydroxyl groups, lignins are intensively studied as candidates to substitute fossil based alcohol and polyol components in polyurethanes, polyesters, epoxides and phenol-formaldehyde resins.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Current lignin research strategies follow two main routes: rst, a direct utilization without chemical modication and second, pre-treatment including chemical modication, functionalization and/or fractionation (degradation) to generate a wide range of intermediates, ne chemicals and polymers. [20][21][22] In between, lignin-derived polymers and composites are also studied as potential materials for biomedical applications such as tissue engineering and drug release. [23][24][25] Due to the large number of hydroxyl groups, lignins are intensively studied as candidates to substitute fossil based alcohol and polyol components in polyurethanes, polyesters, epoxides and phenol-formaldehyde resins.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from lignin self‐association, lignin can also be easily modified chemically because of the presence of many functional groups, such as aromatic groups, phenolic hydroxy groups, alcoholic hydroxy groups, and carbon–carbon double bonds. After appropriate chemical modifications, lignin derivatives can be used in many different areas . The chemical modification of lignin can be classified into three main categories: 1) fragmentation or depolymerization to use lignin as a carbon source or to cleave the lignin structure into aromatic macromers; 2) modification by creating new chemical active sites; 3) chemical modification of hydroxy groups.…”
Section: Biological Activities Of Ligninmentioning
confidence: 99%
“…Owing to its formation of a stable covalent bond between lignin and synthesized polymer, graft copolymerization is considered as one of the most effective methods for lignin modification, which can improve the adhesion of two incompatible phases 36 . Liu et al 37 reported on the excellent biocompatibility between PLA and lignin graft copolymers synthesized using different chiral lactide monomers.…”
Section: Introductionmentioning
confidence: 99%